2006
DOI: 10.1542/peds.2005-0983
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Decreasing Sugar-Sweetened Beverage Consumption on Body Weight in Adolescents: A Randomized, Controlled Pilot Study

Abstract: A simple environmental intervention almost completely eliminated SSB consumption in a diverse group of adolescents. The beneficial effect on body weight of reducing SSB consumption increased with increasing baseline body weight, offering additional support for American Academy of Pediatrics guidelines to limit SSB consumption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
457
3
16

Year Published

2008
2008
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 491 publications
(488 citation statements)
references
References 33 publications
12
457
3
16
Order By: Relevance
“…29 Our review addressed these limitations and aimed to evaluate a broader scope of metabolic health outcomes (beyond weight gain and body composition) focusing on long-term effects and including prenatal exposures. With stringent requirements for long-term outcomes after early NNS exposure (before 12 years of age) and NNS-specific longitudinal analyses demonstrating clearly prospective relationships (baseline NNS exposures associated with subsequent metabolic outcomes), some studies included in previous reviews were excluded from ours because of insufficient duration and evaluation of adolescent populations, 38,39 multifaceted interventions, 40 or unclear temporality of exposure. 41,42 Even with our search strategy improvements, evaluation of new studies, and strict inclusion criteria to reduce heterogeneity and address our modified research question, we have found insufficient evidence to clearly determine whether an association exists between earlylife NNS exposure and long-term metabolic health.…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
“…29 Our review addressed these limitations and aimed to evaluate a broader scope of metabolic health outcomes (beyond weight gain and body composition) focusing on long-term effects and including prenatal exposures. With stringent requirements for long-term outcomes after early NNS exposure (before 12 years of age) and NNS-specific longitudinal analyses demonstrating clearly prospective relationships (baseline NNS exposures associated with subsequent metabolic outcomes), some studies included in previous reviews were excluded from ours because of insufficient duration and evaluation of adolescent populations, 38,39 multifaceted interventions, 40 or unclear temporality of exposure. 41,42 Even with our search strategy improvements, evaluation of new studies, and strict inclusion criteria to reduce heterogeneity and address our modified research question, we have found insufficient evidence to clearly determine whether an association exists between earlylife NNS exposure and long-term metabolic health.…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
“…Many cross-sectional studies have shown a positive association between consumption of sweetened beverages, mainly in teenagers, and body weight [58][59][60][61][62][63][64][65] (reviewed in [66]). Interventional studies further showed that adding sweetened beverages to the usual diet led to an increase in body weight [67,68], while reducing sweetened beverages intake in overweight subjects decreased body weight [69][70][71][72][73]. Several large studies also reported that sweetened beverage consumption increased the risk of developing type 2 diabetes, but this effect was essentially linked to body weight changes [74][75][76].…”
Section: Do Changes In Fructose Consumption Explain the Current Epidementioning
confidence: 99%
“…11,12 In contrast, drinking plain water instead of SSBs is one approach for individuals trying to reduce dietary energy intake and thereby possibly benefit obesity prevention and control. [13][14][15] Hence, consuming water as part of a healthy diet (eg, one that contains fruits, vegetables, whole grains, low-fat/reduced fat dairy, and lean meats) can aid weight management [13][14][15][16] and, if substituted for SSB consumption, also possibly avert the adverse consequences associated with SSB intake such as dental caries, 6 and avoid risks from high levels of SSBs such as developing obesity [2][3][4][5] and type 2 diabetes. 7 One approach for promoting water intake is to make free potable drinking water widely accessible in public facilities, including schools.…”
Section: Introductionmentioning
confidence: 99%